2021
DOI: 10.1017/lap.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the Role of Ideology in Chile

Abstract: Voters’ ideological stances have long been considered one of the most important factors for understanding electoral choices in Chile. In recent years, however, the literature has begun to call this premise into question, due to several changes in the Chilean political landscape: the current crisis of representation, the high programmatic congruence between the two main coalitions, the decline in the political relevance of the dictatorship, and the rise of nonprogrammatic electoral strategies. In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…The coalitions then traded control of executive power until 2022. Over time, these two large political alliances have converged toward the center (Visconti, 2021), 8 which can be explained by the center-left government's decision to keep the market-based reforms introduced by Pinochet during the military dictatorship (Maillet, 2013) and the moderation of the center-right parties that have appropriated elements of social welfare policies (López and Baeza, 2011;López et al, 2013). These traditional coalitions could not adapt to a new social context and failed to include demands from relevant social groups in their platforms (Luna, 2014;Morgan and Meléndez, 2016;Rosenblatt, 2018).…”
Section: The Political Landscapementioning
confidence: 99%
“…The coalitions then traded control of executive power until 2022. Over time, these two large political alliances have converged toward the center (Visconti, 2021), 8 which can be explained by the center-left government's decision to keep the market-based reforms introduced by Pinochet during the military dictatorship (Maillet, 2013) and the moderation of the center-right parties that have appropriated elements of social welfare policies (López and Baeza, 2011;López et al, 2013). These traditional coalitions could not adapt to a new social context and failed to include demands from relevant social groups in their platforms (Luna, 2014;Morgan and Meléndez, 2016;Rosenblatt, 2018).…”
Section: The Political Landscapementioning
confidence: 99%
“…En cierto sentido, la abstención puede convertirse en una alternativa viable cuando la oferta partidaria es insatisfactoria dado que ninguna alternativa es suficientemente convincente para el votante (Kang, 2004). Mientras en Chile la ciudadanía que se identifica con una posición ideológica de derecha es más disciplinada para votar, quienes se ubican a la izquierda en el eje ideológico tienden a ser más apáticos en el ejercicio del voto frente a una oferta programática pro statu quo (Visconti, 2021). En este trabajo buscamos desentrañar este dilema en la sección 3.…”
Section: Participación Electoral Y Canalización De Demandasunclassified
“…Since previous studies have shown that ideology is an important predictor for electoral decisions of Chileans, even when there is discontent with democracy, political parties, and the elites (Visconti, 2021), as migration has become increasingly politicized, we would voters to express views consistent with those adopted by their likeminded parties. However, since we can also assess people's views before parties adopted policy positions, we can verify whether the party' positions were in line with those previously held by their traditional electoral base.…”
Section: Views On Immigrants In Chile Before and After Immigration Be...mentioning
confidence: 99%